2019
DOI: 10.1039/c9cc00328b
|View full text |Cite
|
Sign up to set email alerts
|

Non-reducible disulfide bond replacement implies that disulfide exchange is not required for hepcidin–ferroportin interaction

Abstract: Non-reducible disulfide bond replacement was used to study the disculfide exchange between hepcidin and ferroportin, and the results indicate that the hepcidin–ferroportin interaction does not require disfulfide exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In fact, while preventing Met oxidation during peptide resin cleavages has been thoroughly investigated, 40 Met oxidation during peptide synthesis has been less studied. 41 In fact, in some cases Met oxidation during synthesis can be so cumbersome, that a less oxidation-prone AA instead of Met is used, 42 and we thus set out to investigate the impact of hydroperoxides in NBP, as well as other SPPS solvents, on the oxidation of Met and other oxidizable AAs and peptides. To this end, we evaluated Met oxidation susceptibility in different solvents, determining the content of Fmoc-Met(O)-OH in Fmoc-Met-OH solutions over time (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, while preventing Met oxidation during peptide resin cleavages has been thoroughly investigated, 40 Met oxidation during peptide synthesis has been less studied. 41 In fact, in some cases Met oxidation during synthesis can be so cumbersome, that a less oxidation-prone AA instead of Met is used, 42 and we thus set out to investigate the impact of hydroperoxides in NBP, as well as other SPPS solvents, on the oxidation of Met and other oxidizable AAs and peptides. To this end, we evaluated Met oxidation susceptibility in different solvents, determining the content of Fmoc-Met(O)-OH in Fmoc-Met-OH solutions over time (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The DADA-based disulfide replacement by non-reducible bridges was examined as a potential method to study this phenomenon between hepcidin and ferroportin. [22] Hepcidin is a 25-amino acid peptide containing four disulfide bonds and a key regulator of iron levels in mammals through attenuating the function of the iron transporter ferroportin. Previous studies concluded that the binding between ferroportin and hepcidin may or may not include an intermolecular disulfide exchange step.…”
Section: Hepcidin Analogs With Non-reducible Thioether Bondsmentioning
confidence: 99%
“…Previous studies concluded that the binding between ferroportin and hepcidin may or may not include an intermolecular disulfide exchange step. [22] To clarify this problem, a non-native hepcidin incorporating non-reducible CÀ S bonds in place of native SÀ S bond was synthesized using the DADA approach (Table 2). Four SÀ C bridged hepcidin disulfide surrogates (28, 29, 30, and 31) and four CÀ S bridged hepcidin disulfide surrogates (32, 33, 34, and 35) were synthesized using Allyl/Alloc protected CÀ S and SÀ C bridged diaminodiacids.…”
Section: Hepcidin Analogs With Non-reducible Thioether Bondsmentioning
confidence: 99%
“…In order to circumvent this issue, sulfur atoms have been substituted to replace one sulfur with carbon or oxygen or both sulfurs with carbon, through saturated or unsaturated bridges. The resulting peptide analogues are often comparable to the parent, ,,, with some having more prolonged or greater biological activity . This can be done using ring closing metathesis (RCM) of olefinic residues to create α-helical peptides that penetrate cells more efficiently than the natural peptides .…”
mentioning
confidence: 98%